Educational Psychology as a Field and as a Career. Interview with César Coll - Marco Antonio Rigo Lemini; Frida Díaz Barriga Arceo; Gerardo Hernández Rojas (Universidad Autónoma de Baja California, 2005)
This work offers an interview made by three Mexican scholars to Dr. César Coll from Barcelona University, who is one of the most well-known and influential educational psychologists in the Hispanic academic world. In this interview, Dr. Coll makes important contributions about themes such as: the Educational Psychology epistemological standing, the tendencies in the education of the professionals of this field, the new practices of the profession, some problems related to the accumulation and immeasurability of the psychology knowledge, and about the continuity of the academic and research groups.